GENERAL PERCEPTION ON QUALITY DELIVERY OF HEALTHCARE SERVICES IN GENERAL HOSPITAL KUMO - YAYAJI AHMED, BILKISU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The study is to ascertain the general perception of people on quality delivery of healthcare services in general hospital Kumo Akko LGA, with a view to finding out the changes that are happening with the health sector for proper planning and improvement. The specific objectives are to examine the socio-economic and demographic characteristics of the respondents, to assess the client perception on quality services at the outpatient clinics in Kumo General Hospital and to examine the role of hospital management board in provision of quality healthcare services in Kumo general hospital. Both qualitative and quantitative data were utilised. Data were generated primarily through questionnaire’s and revalidated the data using Nominal Group Technique. 400 respondents were randomly selected. The questionnaire was designed in a five Likert scale with 1= strongly disagree, 2= disagree, 3= neutral, 4=agree and 5= strongly agree. The sociodemographic findings show that majority of the clients were females who had at least a secondary education. The Service quality was assessed using the five SERVQUAL dimensions of Tangibles, Reliability, responsiveness, assurance, empathy and an additional dimension of affordability and accessibility. Majority (60.7%) of respondents agreed that the clinic they were attending was clean. Similarly, majority (59.8%) of respondents agreed that the clinic had a comfortable environment. It can be concluded that clients perceived the service quality at the outpatient’s clinic to be good. The highest score was recorded in the assurance domain while the lowest score was recorded in the responsive domain. The study recommended that Government Health facilities must have an awesome physical environment such as water, sitting facilities, waste disposal, and toilet facilities among others. This will encourage more people to access the service and make the patients to feel more comfortable.